Ultrasound promoted asymmetric transfer hydrogenation of ketones using Ru(II)arene/amino alcohol catalyst system - Shingote, Savita K.; Kelkar, Ashutosh A.; Borole, Yogesh L.; Joshi, Pradip D.; Chaudhari, Raghunath V. (Ultrasonics Sonochemistry, 2008)
Asymmetric transfer hydrogenation of ketones using Ru(II)arene/amino alcohol catalyst system proceeds with significant rate enhancement by ultrasound promotion. Comparison of the silent reactions carried out at 25 degrees C with reactions under sonochemical activation at 25 degrees C clearly showed enhancement in catalytic activity by 5-10 times without significantly affecting the enantioselectivity. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: asymmetric catalysis; transfer hydrogenation; Ultrasound

Catalytic asymmetric transfer hydrogenation of ketones using [Ru(p-cymene)Cl-2](2) with chiral amino alcohol ligands - Deshpande, Sudhindra H.; Kelkar, Ashutosh A.; Gonnade, Rajesh G.; Shingote, Savita K.; Chaudhari, Raghunath V. (Catalysis Letters, 2010)
Catalytic asymmetric transfer hydrogenation of aromatic alkyl ketones has been investigated using [Ru(p-cymene)Cl-2](2) and new derivatives of beta-amino alcohols synthesized from (S)-(-)-lactic acid and mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%). Asymmetric transfer hydrogenation of ketones has been investigated using [Ru(p-cymene)Cl-2](2) and beta-amino alcohols synthesized from (S)-(-)-lactic acid and Mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%).
Keywords: Amino alcohol ligand; Asymmetric transfer hydrogenation; Ketones; Ru catalyst

Environmentally benign synthesis of beta-hydroxy sulfides using cyclic carbonates catalyzed by large-pore zeolites - Upare, Pravin P.; Kinage, Anil K.; Shingote, Savita K.; Gupte, Sunil P. (Green Chemistry Letters and Reviews, 2012)
An efficient one-pot synthesis of beta-hydroxy sulfides from thiophenol and cyclic carbonates catalyzed by large-pore zeolites has been reported. Reaction of thiophenol with ethylene carbonate in the presence of the Na-X zeolite catalyst gave the highest yield of 2-(phenylthio)ethanol (100%), while reaction with propylene carbonate a highest yield of regioselective product 1-(phenylthio)propan-2-ol was obtained (97%). Enantiomerically pure 1,2-propylene carbonate gave highly regioselective and stereospecific phenylthiopropanol, demonstrating that original chirality of propylene carbonate is retained. A plausible mechanism has been proposed for zeolite-catalyzed transformation involving a chemoselective nucleophilic attack of thiophenoloxide ion onto the less-substituted carbon of cyclic carbonate. The Na-X zeolite catalyst is recyclable and provides advantages of green chemistry approach to the synthesis of beta-hydroxy sulfides without the use of any solvent.
Keywords: beta-hydroxy sulfide; ethylene carbonate; propylene carbonate; thiophenol; zeolite

Asymmetric transfer hydrogenation of imines in water/methanol co-solvent system and mechanistic investigation by DFT study - Shende, Vaishali S.; Shingote, Savita K.; Deshpande, Sudhindra H.; Kuriakose, Nishamol; Vanka, Kumar; Kelkar, Ashutosh A. (RSC Advances, 2014)
Asymmetric transfer hydrogenation of various cyclic imines proceeded efficiently with water/methanol co-solvent media in 20 min with excellent yields and enantioselectivities by employing Rh-TsDPEN catalyst and sodium formate as a hydrogen donor. The role of the co-solvent in enhanced productivity of the reaction was investigated by DFT. The mechanism for ATH of the imines has been discussed on the basis of the DFT study.

Asymmetric transfer hydrogenation of imines in water by varying the ratio of formic acid to triethylamine - Shende, Vaishali S.; Deshpande, Sudhindra H.; Shingote, Savita K.; Joseph, Anu; Kelkar, Ashutosh A. (Organic Letters, 2015)
Asymmetric transfer hydrogenation (ATH) of imines has been performed with variation in formic acid (F) and triethylamine (T) molar ratios in water. The F/T ratio is shown to affect both the reduction rate and enantioselectivity, with the optimum ratio being 1.1 in the ATH of imines with the Rh-(1S,2S)-TsDPEN catalyst. Use of methanol as a cosolvent enhanced reduction activity. A variety of imine substrates have been reduced, affording high yields (94-98%) and good to excellent enantioselectivities (89-98%). In comparison with the common azeotropic F-T system, the reduction with 1.1/1 F/T is faster.

Rhodium complex with unsymmetrical vicinal diamine ligand: excellent catalyst for asymmetric transfer hydrogenation of ketones - Deshpande, Sudhindra H.; Shende, Vaishali S.; Shingote, Savita K.; Chakravarty, Debamitra K.; Puranik, Vedavati G.; Chaudhari, Raghunath V.; Kelkar, Ashutosh A. (RSC Advances, 2015)
New unsymmetrical vicinal diamine ligands with systematic variation in the regio and stereo positions in the amine and sulphonamide groups were synthesized from cheap starting material such as norephedrine. Catalytic Asymmetric Transfer Hydrogenation (ATH) of aromatic alkyl ketones has been investigated using transition metal complexes and new derivatives of monotosylated unsymmetrical vicinal diamine ligands using sodium formate as the hydrogen source, in water and methanol. Chiral secondary alcohols were obtained with excellent enantioselectivity (>95% ee) and conversion of ketones (>95%) with [Rh(Cp*)Cl-2](2) and ligand 4 as a catalyst. Enantioselectivity was found to be slightly higher with the use of methanol as a solvent for ATH of ketones with sodium formate as the hydrogen source compared to water as a solvent and was found to be consistent with all the ketones investigated. The reaction mixture is homogeneous in methanol unlike in water, where substrate and product are insoluble in water and form separate phase, sodium formate being soluble in water. The activity and enantioselectivity obtained for ATH of ketones using [Rh(Cp*)Cl-2](2) and unsymmetrical vicinal diamine ligand as catalyst was comparable with the C2 symmetric benchmark ligands like TsDPEN ((1R, 2R)-N-(p-tolylsulfonyl)-1,2-diphenylethylene- diamine), and TsCYDN ((1R, 2R)-N-(p-tolylsulfonyl)-1,2-cyclohexyl, diamine) under similar reaction conditions. To the best of our knowledge, this is first example of the ATH of ketones with good activity and high enantioselectivity with [Rh(Cp*)Cl-2](2) and unsymmetrical vicinal diamine ligands as catalyst systems.

Asymmetric transfer hydrogenation of cyclic imines in water with a versatile hydrogen donorformic acid/N-methylpiperidine: rapid access to highly enantioselective amines - Shende, Vaishali S.; Shingote, Savita K.; Deshpande, Sudhindra H.; Kelkar, Ashutosh. A. (Chemistryselect, 2016)
Asymmetric transfer hydrogenation (ATH) of cyclic imines in water has been investigated for the first time by using HCOOH in combination with bases other than triethylamine as H donor. Effect of FA/Base ratio has shown significant impact on activity and enantioselectivity for ATH reaction in water. Use of methanol as a co-solvent improved the reduction performance. FA/N-methylpiperidine was found to be excellent, versatile hydrogen donor for ATH of imine 6,7-dimethoxy-1-methyl-3,4-dihy-droisoquinoline (1a) giving by far the highest noted TOF value of 5940 h(-1). ATH of-different imines derivatives including 3, 4-dihydoisoquinolines, beta-carbolines and cyclic sulfonyl imines have been performed with excellent activity (91-99% yield) and enantioselectivity (88-97%) in very short time (1-2 min). This is very simple protocol for rapid access to enantioselective amines with very new and versatile hydrogen donor 1.1 FA/Nmethylpiperidine.

A detailed study on heat of reaction and heat rate determination of nitrobenzene hydrogenation to aniline reaction using power compensation reaction calorimeter - Kumar, Rajendra; Mane, Pradip R.; Shingote, Savita K.; Mali, Nilesh A. (Process Safety Progress, 2025)
The present study reports experimental heat of reaction and heat rate data of nitrobenzene hydrogenation to aniline reaction with process parameter variation. A high-pressure isothermal power compensation reaction calorimeter was used for this work. A systematic and step-by-step procedure is also reported to determine the heat of reaction and heat rate for a highly exothermic reaction. The sensitivity of experimental molar heat of reaction (kJ/mol) and evolved heat rate (W) values for nitrobenzene hydrogenation reaction was analyzed for various important process parameters, such as temperature, pressure, substrate quantity, solvent quantity, catalyst quantity, RPM, and hydrogen feed rate. Nitrobenzene hydrogenation reactions were conducted using ethanol as solvent and 5% Pd/C as a catalyst with 55-65 degrees C temperature and 7-9 Bar absolute pressure range. More than 99.99% conversion of nitrobenzene to aniline was obtained, and no other by-products were found. The average experimental nitrobenzene hydrogenation heat of reaction of 21 different experiments was found to be -581.87 kJ/mol, and the maximum heat rate during the nitrobenzene hydrogenation reaction was found to be 16.16 W for experiments using 10 gm of nitrobenzene in solvent.
Keywords: heat of reaction; heat rate; Hydrogenation; nitrobenzene; power compensation; reaction calorimeter